2005
DOI: 10.1177/0895904804270776
|View full text |Cite
|
Sign up to set email alerts
|

An Innovative Look, a Recalcitrant Reality: The Politics of Principal Preparation Reform

Abstract: Concerns about the effectiveness of traditional preparation programs have yielded a wide-ranging debate about new approaches to recruiting and preparing leaders. The resulting policy debate features two general camps: those who wish to refine and bolster the existing system of preparation and licensure and those who advocate a move away from licensure and the attendant notions of leadership that hold sway today. The proponents of conventional preparation have shown a remarkable willingness to compromise, givin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
78
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
4
4
2

Relationship

1
9

Authors

Journals

citations
Cited by 80 publications
(79 citation statements)
references
References 5 publications
0
78
1
Order By: Relevance
“…But some researchers and policymakers have suggested that licensure criteria focused on graduate credits do little to promote high-quality leadership at a time when school leaders are expected to continuously raise student achievement (Campbell & Gross, 2012;Levine, 2005). They have also argued that the cost of a graduate degree may arbitrarily deter talented individuals from pursuing school leadership roles and limit the diversity of principal labor force (Campbell & Gross, 2012;Hess & Kelly, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…But some researchers and policymakers have suggested that licensure criteria focused on graduate credits do little to promote high-quality leadership at a time when school leaders are expected to continuously raise student achievement (Campbell & Gross, 2012;Levine, 2005). They have also argued that the cost of a graduate degree may arbitrarily deter talented individuals from pursuing school leadership roles and limit the diversity of principal labor force (Campbell & Gross, 2012;Hess & Kelly, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Instructional approaches that deviated from the didactic lectures of the traditional programs were viewed positively by the internsespecially in terms of developing leadership skills and dispositions (Hess & Kelly, 2005;Knapp et al, 2006). Interns were enthusiastic not so much about the experience of techniques such as the 360-degree project leader evaluation but more so about the self-development and selfawareness that such techniques induced.…”
Section: Discussionmentioning
confidence: 99%
“…Standalone programs are the result of longstanding dissatisfaction with the disconnect between theory and practice in leadership preparation and the practitioner belief that many holding administrator licensure are unqualified to take on new demands placed on educational leaders (Hess & Kelly, 2005). Standalone programs are the result of longstanding dissatisfaction with the disconnect between theory and practice in leadership preparation and the practitioner belief that many holding administrator licensure are unqualified to take on new demands placed on educational leaders (Hess & Kelly, 2005).…”
Section: Leadership Development For Aspiring Administratorsmentioning
confidence: 99%